Competency-Based Approach to Training Future Teachers-Bachelors of Primary Education - Shkvyr, Oksana; Dudchak, Halyna; Polianovska, Olha (Pedagogical Discourse, 2025)
The article focuses on the need to train future bachelor teachers in the specialty A 3 Primary Education on the Basis of a Competency-Based approach. It is determined that the competency-based approach determines the need to rethink the purpose of training future bachelor teachers in primary education, the results of their learning, educational components (EC) and pedagogical tools of professional activity of teachers of higher educational institutions. The purpose of the article is to highlight the pedagogical conditions for training future bachelor teachers in primary education on the basis of a competency-based approach and the experience of teachers of the Department of Pedagogy of Khmelnytskyi Humanitarian-Pedagogical Academy (KhHPA) regarding their implementation in the process of teaching educational components. The essence of the concepts of «competence», «professional competence», «competence approach» has been clarified. The author’s definition of the concept of «competence approach to the training of future teachers-bachelors of primary education» has been proposed. Based on the study of scientific works, surveys of primary school teachers and the method of expert assessments, the pedagogical conditions for the training of future teachers-bachelors of primary education on the basis of the competency approach have been determined: formation of a value-based and personal attitude of future teachers-bachelors to the acquisition of professional competencies; introduction of practice-oriented teaching technologies into the educational process and the use of competency-oriented tasks for independent work of education seekers. The experience of teachers of the Khmelnytskyi Humanitarian-Pedagogical Academy in implementing certain pedagogical conditions in the process of teaching the following educational components has been highlighted: «Didactics», «Theory and Methods of Education», «Methodology of the Work of the Class Teacher», «Fundamentals of Scientific Research», «Inclusive Education». It is concluded that certain pedagogical conditions contribute to the formation of professional competencies of future teachers-bachelors of primary education. It is noted that further scientific research should be directed to studying foreign experience of professional training of future teachers-bachelors of primary education on the basis of the competency-based approach.